2012
DOI: 10.1155/2012/127485
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic Breast Density Patterns in Asymptomatic Mexican Women

Abstract: Breast density (BD) is a risk factor for breast cancer. Aims. To describe BD patterns in asymptomatic Mexican women and the pathological mammographic findings. Methods and Material. Prospective, descriptive, and comparative study. Women answered a questionnaire and their mammograms were analyzed according to BI-RADS. Univariate (χ 2) and conditional logistic regression analyses were performed. Results. In 300 women studied the BD patterns were fat 56.7% (170), fibroglandular 29% (87), heterogeneously dense 5.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In Mexico, BC is a public health problem because it is the main cause of death by malignant tumours in women of reproductive age [ 1 ]. In this study, we observed that BC was often detected before of 50 years of age, similar to what has been reported by other authors in the Mexican population [ 15 , 16 ]. This observation confirms that this pathology is detected in Mexican women a decade before the normal age of onset in other countries [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Mexico, BC is a public health problem because it is the main cause of death by malignant tumours in women of reproductive age [ 1 ]. In this study, we observed that BC was often detected before of 50 years of age, similar to what has been reported by other authors in the Mexican population [ 15 , 16 ]. This observation confirms that this pathology is detected in Mexican women a decade before the normal age of onset in other countries [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Screening US in women with dense breasts and negative MG can yield an incremental increase in the cancer detection rate of 3.7 to 4.2 more cancers identified per 1000 women screened. [ 6 , 7 , 15 ] Asian women, compared with Western women, more often have small, dense breasts, [ 16 ] and US is an appropriate tool for breast cancer detection in these women. [ 17 ] In our study, 421 (88.6%) small cancers were detected by US, which was higher than MG, and we demonstrated that US was significantly better than MG at detecting malignancy in patients with high breast density.…”
Section: Discussionmentioning
confidence: 99%
“…[24252627] However, some factors such as obesity could modify this because of the inverse relationship between body mass index and mammographic density. [272829] There are conflicting reports, with some reporting an association between breast density pattern and menopausal status, while another demonstrated contrasting results. [21830]…”
Section: Discussionmentioning
confidence: 99%